If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3z + -17 = -9 + z Reorder the terms: -17 + 3z = -9 + z Solving -17 + 3z = -9 + z Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '-1z' to each side of the equation. -17 + 3z + -1z = -9 + z + -1z Combine like terms: 3z + -1z = 2z -17 + 2z = -9 + z + -1z Combine like terms: z + -1z = 0 -17 + 2z = -9 + 0 -17 + 2z = -9 Add '17' to each side of the equation. -17 + 17 + 2z = -9 + 17 Combine like terms: -17 + 17 = 0 0 + 2z = -9 + 17 2z = -9 + 17 Combine like terms: -9 + 17 = 8 2z = 8 Divide each side by '2'. z = 4 Simplifying z = 4
| 2x^2-26x=-84 | | (6x+4)-(2x+6)=2x | | 6(2f+5)=18 | | 18a+b-3a+14b= | | 1+2x=-23-4x | | 81+81+81= | | 2(5x+2)=-16 | | x(.75)=55000 | | 30+30+30+30= | | X+75+x=153 | | (5x-3)(4x+5)=0 | | 25^2/x=5 | | 8x-13+5x=5+9x+14 | | 9x+1.28=3x+11 | | -11-y=1 | | y^2+2h=35 | | y=2.5(3)+3 | | 0.3x+0.6=-1.8 | | y=2.5(2)+3 | | 1-Y+2Z=3 | | X+75+x=159 | | 2r^2-5t=12 | | -5y+10=55 | | y=2.5(1)+3 | | y=2.5(0)+3 | | 3(4-2d)-6=(5d-5) | | 2(3x-7)=8x-28 | | ((-3x^2)+144)=0 | | 8x-13+5x=5+9x+6 | | 6.9a+6.52=-57.65 | | q=2p+4 | | y=2.5(-1)+3 |